Editorial: Introduction to the Special Issue on AI, Machine Learning, and Deep Learning: Advances and Applications for EMC - Duffy, Alistair; Liu, En-Xiao (IEEE transactions on electromagnetic compatibility, 2024)
Not many technologies have ever captured the public imagination as widely and abruptly as artificial intelligence (AI). While AI has been a staple of science fiction for decades with actual applications in engineering and sciences for many years, it is only in the last year or so that generative AI tools have enthused and engaged so many people. All of a sudden, our general consciousness sees AI as so accessible and so normalized. This is particularly evident that you wish to do a simple web search of AI tools available online or perhaps check out the libraries and toolboxes of your favorite programming languages.